A global database of soil seed bank richness, density, and abundance - Auffret, Alistair; Ladouceur, Emma; Haussmann, Natalie; Daouti, Eirini; Elumeeva, Tatiana; Kačergytė, Ineta; Knape, Jonas; Kotowska, Dorota; Low, Matthew; Onipchenko, Vladimir; Paquet, Matthieu; Rubene, Diana; et al. (Swedish University of Agricultural Sciences, 2024)
A soil seed bank is the collective name for viable seeds that are stored naturally in the soil. This database is the result of a comprehensive literature search, including all seed bank studies from the Web of Science from which data could be extracted, as well as an additional search of the Russian language literature. The database contains information on the species richness, seed density and/or seed abundance in 3096 records from at least 1778 locations across the world’s seven continents, extracted from 1442 studies published between 1940 and 2020. Records are grouped into five broad habitat categories (aquatic, arable, forest, grassland and wetland), including information relating to habitat degradation from, or restoration to other habitats (total 14 combinations). Sampling protocols were also extracted for each record, and the database was extensively checked for errors. The location of each record was then used to extract summary climate data and biome classification from external published databases (Karger et al. 2017, 2018 and Olson et al. 2001, respectively).

A full data descriptor for this dataset is published as a data paper in the journal Ecology. As such, the data are described according to the journal's specifications in the file MetadataS1.pdf, with additional information in data_entry_intructions.pdf. The initial version of the dataset is also published as supporting information to the data paper. The file DataS1.zip described in MetadataS1.zip contains the files gsb_db.csv, gsb_code.R and data_entry_intructions.pdf.


References:
Karger, D. N., O. Conrad, J. Böhner, T. Kawohl, H. Kreft, R. W. Soria-Auza, N. E. Zimmermann, H. P. Linder, and M. Kessler. 2017. Climatologies at high resolution for the earth’s land surface areas. Scientific Data 4:170122. https://doi.org/10.1038/sdata.2017.122

Karger, D. N., O. Conrad, J. Böhner, T. Kawohl, H. Kreft, R. W. Soria-Auza, N. E. Zimmermann, H. P. Linder, and M. Kessler. 2018. Data from: Climatologies at high resolution for the earth’s land surface areas. Dryad Digital Repository. http://dx.doi.org/doi:10.5061/dryad.kd1d4

Olson, D. M., E. Dinerstein, E. D. Wikramanayake, N. D. Burgess, G. V. N. Powell, E. C. Underwood, J. A. D’amico, I. Itoua, H. E. Strand, J. C. Morrison, C. J. Loucks, T. F. Allnutt, T. H. Ricketts, Y. Kura, J. F. Lamoreux, W. W. Wettengel, P. Hedao, and K. R. Kassem. 2001. Terrestrial Ecoregions of the World: A New Map of Life on Earth A new global map of terrestrial ecoregions provides an innovative tool for conserving biodiversity. BioScience 51:933–938. Link to data: https://files.worldwildlife.org/wwfcmsprod/files/Publication/file/6kcchn7e3u_official_teow.zip

En fröbank är namnet på de frön som vilar naturligt i jorden. Databasen innehåller data angående antalet arter, antalet frön samt densitet av frön per ytenhet från 1442 studier publicerade mellan 1940 och 2020. Studierna identifierades genom en bred sökning i Web of Science, samt en separat sökning av artiklar publicerade i det ryska språket. Databasen innehåller även information gällande livsmiljö, klimat och biom. Se även mer utförlig engelsk beskrivning.

En databeskrivning för datamängden har publicerats som dataartikel i tidskriften Ecology. Därför beskrivs data enligt tidskriftens specifikationer i filen MetadataS1.pdf, med ytterligare information i data_entry_instructions.pdf. Den första versionen av datamängden publiceras parallellt som ett appendix till artikeln. Filen DataS1.zip som beskrivs i MetadataS1.pdf innehåller filerna gsb_db.csv, gsb_code.R and data_entry_intructions.pdf.


Referenser:
Karger, D. N., O. Conrad, J. Böhner, T. Kawohl, H. Kreft, R. W. Soria-Auza, N. E. Zimmermann, H. P. Linder, and M. Kessler. 2017. Climatologies at high resolution for the earth’s land surface areas. Scientific Data 4:170122. https://doi.org/10.1038/sdata.2017.122

Karger, D. N., O. Conrad, J. Böhner, T. Kawohl, H. Kreft, R. W. Soria-Auza, N. E. Zimmermann, H. P. Linder, and M. Kessler. 2018. Data from: Climatologies at high resolution for the earth’s land surface areas. Dryad Digital Repository. http://dx.doi.org/doi:10.5061/dryad.kd1d4

Olson, D. M., E. Dinerstein, E. D. Wikramanayake, N. D. Burgess, G. V. N. Powell, E. C. Underwood, J. A. D’amico, I. Itoua, H. E. Strand, J. C. Morrison, C. J. Loucks, T. F. Allnutt, T. H. Ricketts, Y. Kura, J. F. Lamoreux, W. W. Wettengel, P. Hedao, and K. R. Kassem. 2001. Terrestrial Ecoregions of the World: A New Map of Life on Earth A new global map of terrestrial ecoregions provides an innovative tool for conserving biodiversity. BioScience 51:933–938. Link to data: https://files.worldwildlife.org/wwfcmsprod/files/Publication/file/6kcchn7e3u_official_teow.zip
A global database of soil seed bank richness, density, and abundance
Keywords: seed bank; species; arter; plant species richness; dispersal; Species distribution; Arters utbredning; plants; växter; biodiversity; biodiversitet; Ecology; Ekologi; Biota; Biologi och ekologi